The Relationship Between Alexithymia and Mobile Phone Addiction Among Mainland Chinese Students: A Meta-Analysis - Huang, Haitao; Wan, Xiao; Lu, Guangli; Ding, Yueming; Chen, Chaoran (Frontiers in Psychiatry, 2022)
Alexithymia and mobile phone addiction are common phenomena in our daily life. Many studies have explored the internal relationship between them based on different theoretical perspectives, but the extent of the exact correlation is still controversial. In order to address this controversy and clarify the reasons for the divergence, a meta-analysis of 26 articles comprising 23387 Chinese students was conducted. The results show that alexithymia was highly positively correlated with mobile phone addiction (r = 0.41, 95% CI = [0.37, 0.45]); Furthermore, the relationship was regulated by mobile phone addiction measurement tool and year of publication, with studies using MPATS having higher correlation coefficients than those using MPAI or other measurement tools. Studies published in 2020-2021 yielded higher correlations than those published in 2014-2016 and 2017-2019. However, the relationship was not regulated by gender, region, or the measures of alexithymia. Longitudinal studies or experimental studies should be strengthened in the future to further establish the direction(s) of causality for the relation between alexithymia and mobile phone addiction.